The law and purity in Matthew; Jesus touching a bleeding woman and a dead girl (Mt 9:18-26) - Viljoen, Francois (Nederduitse Gereformeerde Teologiese Tydskrif, 2014)
This article investigates the double story in Matthew of Jesus touching a woman with blood flow and a dead girl, with specific reference to purity regulations of the Hebrew Bible. According to Matthew it seems that Jesus did not perform any purity rituals after touching the impure woman and girl. Such negligence would have caused serious repercussions amongst the spectators. In the Sermon on the Mount Jesus explicitly states that He did not come to abolish the Law, but in this double story Jesus apparently abrogates purity regulations. It is suggested that Matthew purposefully describes these events to demonstrate how these Laws found their fulfilment in Jesus. Jesus is depicted as Emmanuel and Saviour. Instead of Him being polluted by touching these persons, Jesus cleanses the impure woman and raises the dead girl to life. As Holy One purity flowed from Him to the defiled persons, so that they could be cleansed without Him being polluted. These acts of Jesus form part of the coming of the Kingdom of heaven. By accepting Jesus as their saviour, the Matthean community shares the benefits of his purifying power. Their purity is no longer dependent on external purity regulations, but on the cleansing power of Jesus, the Holy One.